Light shutter using dye-doped cholesteric liquid crystals with polymer network structure. Issue 1 (2nd January 2017) - Yu, Byeong-Hun; Ji, Seong-Min; Kim, Jin-Hun; Huh, Jae-Won; Yoon, Tae-Hoon
ABSTRACT: Proposed herein is a light shutter using dye-doped cholesteric liquid crystals with a polymer network structure for a high-visibility see-through display. The proposed light shutter shows an initially focal-conic state by forming the polymer network structure at the focal-conic state. The proposed light shutter can be easily switched between the focal-conic and homeotropic states without a complicated drive scheme.